Female Directors' Foreign Experience and Environmental and Sustainable Performance. (9th May 2022) - Ullah, Farid; Jiang, Ping; Ntim, Collins G.; Shahab, Yasir; Jiang, Xianling
Abstract: We examine the impact of female directors' foreign experience on environmental and sustainable (ES) performance in Chinese listed firms from 2010 to 2016. We find that female directors' foreign experience, especially work experience, significantly positively impacts firms' ES performance. The results are robust, and self‐selection concerns are addressed using the Heckman two‐step model and propensity score matching. Also, female directors' foreign experience impacts ES performance more significantly when female directors gain foreign experience from a Scandinavian law country or a civil law country. Overall, our results reveal that female directors with foreign experience transmit ES knowledge and practices to Chinese firms.